The temporospatial control of Tfh cells. Issue 1 (1st January 2014) - Yu, Di; Linterman, Michelle
Abstract : The January 2014 issue contains a Special Feature on The Temporospatial Control of Tfh Cells . The reviews featured bring together an enormous amount of insight into Tfh biology: they demonstrate that we have a good understanding of Tfh differentiation and function, but that there is still more to be learned about the intriguing population of helper T cells specialised to help B cells. Furthermore, they outline how important this subset is in both health and disease, and demonstrate that furthering our knowledge of this subset will have implications for improving the efficacy of vaccination, the control of infection, the treatment of both autoimmunity and immunodeficiency and even understanding the outcome of a number of different types of cancer. Immunology and Cell Biology would like to thank the coordinators of this Special Feature – Di Yu and Michelle Linterman – for their planning and input. Further background information on this important topic is available through the accompanying web focus which links to related articles from across Nature Publishing Group.